(untitled) (MATEMATIKA, 2013)
The Population and Housing Census remains vital as the main source of data collection aimed at providing a comprehensive set of statistical information about the population in the country in terms of its size and spatial distribution, its demographic, social and economic characteristics as well as housing stock at a specific time reference. The census provides essential information for policy development and planning, for managing and evaluating programmes activities across a broad spectrum of sectors and for monitoring overall progress. The Census being a total coverage and complete count of the population, household and living quarters at a given time enables to provide for a wide scope of enquiry even to the extent to meet the demand for data on small areas statistics. The United Nations Statistical Commission launched the current 2010 World Population and Housing Census Programme covering a 10 year period from 2005-2014. It urges member states to carry a population and housing at least once over the above said period. Malaysia, launched the fifith decennial Population and Housing Census in July 2010 which provides a wealth of information on the population and household with demographic and socio-economic characteristics as well as housing stock. The 2010 Census round witnessed increased interest and use of improved technologies and new approaches in the different phases of the census operation. The emerging improved technologies are transforming the way the Census are conducted in terms of operation management, quality assurance, data capture, mapping (GIS, GPS), data processing and storage. Among the new approaches used during the Census are the use of internet based questionnaire for data collection, alternative publicity strategies being implemented and the web-based data dissemination. Even small improvements in census technology can result in important gains in the quality and cost-effectiveness of the whole census operation and still maintain the confidentiality of data. This paper outlines how the Department of Statistics Malaysia adopted new approaches and technologies during the 2010 Census. Highlights will also be given on the impact of the new technologies in the implementation of Census and the way forwardness. Keywords: Population and Housing Census 2010 Mathematics Subject Classification: 62P25